Menakar Ulang Batas Usia Perkawinan: Edukasi Hukum atas Dispensasi Kawin dan Implikasinya dalam Pencegahan Stunting di Kalangan Pelajar - Nurrahman Fajrul Sinrang; Firman Husain (Universitas Muhammadiyah Manado, 2026)
Child marriage remains a significant issue negatively impacting the health and quality of the younger generation, particularly through the increased risk of stunting in children. This article discusses the results of an educational outreach titled “Marriage Is Not Just About Legality: Legal Education on Marriage Dispensation and Its Implications for Stunting Prevention Among Students,” conducted at SMA Negeri 3 Parepare. The outreach aimed to raise students’ awareness about the relationship between minimum marriage age, marriage dispensation, and the health impacts on children, especially the risk of stunting. The methods employed included deconstruction, brainstorming, material delivery, reconstruction, and evaluation through pre-test and post-test assessments. Results demonstrated a significant improvement in students’ understanding from both medical and legal perspectives. The discussion focused on analyzing the contradictory legal norms regarding minimum marriage age and marriage dispensation, which frequently lead to implementation challenges. This outreach underscores the importance of integrating legal education and reproductive health as a preventive strategy to reduce child marriage and prevent stunting. Consequently, the program contributes to shaping a healthy, legally aware younger generation capable of making mature and responsible marriage decisions.